2015
DOI: 10.1007/s13762-015-0838-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of crude petroleum on water repellency in a clayey alluvial soil

Abstract: Water repellency was studied in a clayey soil contaminated with light (36.6°API), medium (27.4°API), and heavy (15.0°API) crude oils at concentrations of 1, 2, 4, and 8 %. Higher water drop penetration times (WDPTs) were observed in dry soil as the density and concentration of petroleum increased, resulting in logarithmic functions which could be modeled from API gravity and oil concentration (R 2 = 0.986). WDPTs varied from 2.1 to 8.7 s with light crude, 11.1 to 44.9 s for medium crude, and 39.4 to 134.5 s fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Other properties evaluated were the content of textures, densities and porosity, these parameters are intrinsically related to soil compaction and respiration (González-Cueto et al, 2009); under this argument, the results of apparent and real density expressed in Table 5 were contrasted, it was observed that when polluting, both have a slight increase (DA of ~ 7% and DR of ~ 2%) but with signif icant differences with respect to control (P < 0.05), when applying the treatments, cation exchange DA and DR increases ~ 17% and ~ 11% respectively in comparison with noncontaminated soil, however, the values obtained for this same variables in natural attenuation decrease and do not they change after of weathering (P > 0.05), when comparing these results with those of control soil; no signif icant differences were found (P > 0.05). In relation to the above, there are studies that mention that changes in soil densities after being contaminated may be related to the formation of higher molecular weight aggregates as compounds are deposited mainly in clays (Suthersan et al, 2016;Marín-García et al, 2016), these effects can be measured in the increase of densities (compaction), decrease in clay content and increase in sands (decrease in f ield capacity, as well as signif icant changes in porosity (generally decrease; Gutiérrez and Zavala, 2002;Khamehchiyan et al, 2007;Maldonado-Chávez et al, 2010); all these investigations can justify the decrease in porosity (% Po), the slight increase in sands (% A) and decrease in clays (% R) in contaminated soil with respect to the control, after the two restoration processes, it can be seen that there are different behaviors, in the case of ICF, there is a change in textures where % A goes from ~ 60% in contaminated to ~ 80% in treated and, thus, remains in ICI (79%, P > 0.05), reflecting in the decrease of % R (from 20% in contaminated to 10% in ICF and ICI, P > 0.05), in the case of % Po, this is lower by ~ 15% after treatment and drops to ~ 25% after one year, it is important to mention that the textural classif ication in the samples treated by CI is sandy-loam compared to the control that is loam-claysandy, also this phenomenon can be related that in the study zone there is forage grass so it does not trampling by livestock is ruled out (Rucks et al, 2004;Zamora et al, 2012). In discrepancy, when evaluating the results of % Po and textures of the treatment by AN, we obtained what % Po recovers to similar values of the control and, although there are signif icant differences in the textures (P < 0.05), the classif ication coincides with the witness.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other properties evaluated were the content of textures, densities and porosity, these parameters are intrinsically related to soil compaction and respiration (González-Cueto et al, 2009); under this argument, the results of apparent and real density expressed in Table 5 were contrasted, it was observed that when polluting, both have a slight increase (DA of ~ 7% and DR of ~ 2%) but with signif icant differences with respect to control (P < 0.05), when applying the treatments, cation exchange DA and DR increases ~ 17% and ~ 11% respectively in comparison with noncontaminated soil, however, the values obtained for this same variables in natural attenuation decrease and do not they change after of weathering (P > 0.05), when comparing these results with those of control soil; no signif icant differences were found (P > 0.05). In relation to the above, there are studies that mention that changes in soil densities after being contaminated may be related to the formation of higher molecular weight aggregates as compounds are deposited mainly in clays (Suthersan et al, 2016;Marín-García et al, 2016), these effects can be measured in the increase of densities (compaction), decrease in clay content and increase in sands (decrease in f ield capacity, as well as signif icant changes in porosity (generally decrease; Gutiérrez and Zavala, 2002;Khamehchiyan et al, 2007;Maldonado-Chávez et al, 2010); all these investigations can justify the decrease in porosity (% Po), the slight increase in sands (% A) and decrease in clays (% R) in contaminated soil with respect to the control, after the two restoration processes, it can be seen that there are different behaviors, in the case of ICF, there is a change in textures where % A goes from ~ 60% in contaminated to ~ 80% in treated and, thus, remains in ICI (79%, P > 0.05), reflecting in the decrease of % R (from 20% in contaminated to 10% in ICF and ICI, P > 0.05), in the case of % Po, this is lower by ~ 15% after treatment and drops to ~ 25% after one year, it is important to mention that the textural classif ication in the samples treated by CI is sandy-loam compared to the control that is loam-claysandy, also this phenomenon can be related that in the study zone there is forage grass so it does not trampling by livestock is ruled out (Rucks et al, 2004;Zamora et al, 2012). In discrepancy, when evaluating the results of % Po and textures of the treatment by AN, we obtained what % Po recovers to similar values of the control and, although there are signif icant differences in the textures (P < 0.05), the classif ication coincides with the witness.…”
Section: Resultsmentioning
confidence: 99%
“…To remedy these sites, different proposals have been carried out, some have managed to re-establish the vocation of use, despite this, and there still problems after restoration such as toxicity and water repellency (Fawzy, 2008;Yongming, 2009;Arao et al, 2010). In this sense, several investigations have shown the importance of evaluating the bioaccumulation of metals and aromatic compounds after remediation work and have emphasized that the behavior of the pollutant depends on the specif ic conditions of each region, in some cases, the contaminants can be transferred in the middle and in this way reach the human being, there are also sites in which the hydrocarbons are below the regulatory limit and have negative impacts on the development of some plants, while others are above this limit, they do not present affectations; different researchers have emphasized that in order to restore a site, different alternatives must be evaluated and the long-term eff iciency of each of them must be compared, in such a way that the information generated can serve as a decision-making tool to restore the properties of the site, optimally, feasibly and adequately (Liang et al, 2011;Hou and Al-Tabbaa, 2014;Bolan et al, 2014;Marín-García et al, 2016;Lu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…They mentioned that the reduction in the electrostatic interaction between soil particles and water enhanced by a thin film of low-polarity of the compounds (i.e., hydrocarbons), around the polar surfaces of the soil organic matter (SOM) and clays, could be the reason (Adams et al, 2008a and2008b). When dry, a film of petroleum hydrocarbon covers soil particles, bind them together and on the surface, it form a crust (Marı´n-Garcı et al, 2016). Large hydrocarbon molecules at the soil surface persist and glue the soil particles to form crust.…”
Section: Phytoremediation Of Hc and Soil Moisture Statusmentioning
confidence: 99%
“…Heavy crude oil and extra heavy crude oil are highly viscous; under normal reservoir conditions cannot easily flow to production wells. It also has a high mass density and an American Petroleum Institute (API) gravity of 20°or less [16]. According to Eqs.…”
Section: Introductionmentioning
confidence: 99%